THE ORIGIN OF FLUORIDE IN GROUNDWATER SUPPLY TO HERMOSILLO CITY, SONORA, MÉXICO - Valenzuela-Vásquez L.; Ramírez-Hernández J.; Reyes-López J.; Sol-Uribe A.; Lázaro-Mancilla O. (My University, 2006)
Anomalous high fluoride concentration up to 7.59 mg/dm3 is found in groundwater from “La Victoria” area. This water is used to supply drinking water to Hermosillo City, Sonora. Geochemistry of groundwater, relationship between physicochemical parameters, hydrogeology and geologic setting were correlated to define the origin and the geochemical mechanisms of groundwater fluorine enrichment. High fluoride concentration is associated with high bicarbonates, pH and temperature, and it decreases toward the west and south of the area. Fluoride is in negative correlation to calcium concentration. Sodium sulphate facies of regional deep water flow are related to high fluoride concentration. High electric resistivity rocks associated with granites from the Sierra Bachoco basement might be the deep source of fluoride. Outcropping of Sierra Bachoco in the west causes upward regional flow. Groundwater of longer residence time can be pumped there. The anomalous area is restricted to “La Victoria” because calcareous paleozoic rocks outcrop to the south.
Keywords: FLUORINE; GROUNDWATER; CONTAMINANT FLUORIDE; HERMOSILLO CITY MÉXICO